2015
DOI: 10.5812/ircmj.16552
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Zataria multiflora Essence on Experimentally Contaminated Acryl Resin Plates With Candida albicans

Abstract: Background:Adherence and colonization of Candida species particularly C. albicans on denture surfaces, forms a microbial biofilm, which may result denture stomatitis in complete denture users.Objectives:The purpose of the present study was to evaluate the antifungal effect Zataria multiflora essence in removing of Candida albicans biofilms on experimentally contaminated resin acryl plates.Materials and Methods:In the present experimental study, 160 resin acrylic plates (10 × 10 × 1 mm) were contaminated by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
3
Order By: Relevance
“…Based on this study, a solution of 1% or 0.1% of ZM could be as effective as penicillin/nystatine (completely eliminating the S. mutans and C. albicans). Jafari et al (31) also reported that higher concentrations of ZM were more comparable to nystatine in regard to elimination of C. albicans of acrylic plates. The reason of testing very small percentages of ZM in this study was to obtain the minimum effective dosage of ZM since no study has been done so far on adverse effects and citotoxicity of ZM.…”
Section: Discussionmentioning
confidence: 95%
“…Based on this study, a solution of 1% or 0.1% of ZM could be as effective as penicillin/nystatine (completely eliminating the S. mutans and C. albicans). Jafari et al (31) also reported that higher concentrations of ZM were more comparable to nystatine in regard to elimination of C. albicans of acrylic plates. The reason of testing very small percentages of ZM in this study was to obtain the minimum effective dosage of ZM since no study has been done so far on adverse effects and citotoxicity of ZM.…”
Section: Discussionmentioning
confidence: 95%
“…Dentre os protocolos de desinfecção, a higienização mecânica por meio da escovação, assim como higienização química por imersão em soluções como HS, digluconato de clorexidina, hexetidina, perborato de sódio, vinagre, dentre outros, são as mais comuns (Castro et al, 2015;Sczepanski et al, 2014;Aoun et al, 2015). Paralelamente, métodos alternativos como a desinfecção pela energia de micro-ondas, por luz ultravioleta, por plasma e a utilização de produtos químicos de limpeza como sabonetes, pastilhas efervescentes e enxaguatórios bucais também vêm sendo utilizados para este fim (Asnaashari, Motamedi, Asnaashari, & Azari-Marhabi, 2019;Jafari, Tafti, Hoseiny, & Kazemi, 2015;Zoccolotti et al, 2018;Sharma, Garg, & Kalra, 2017;Asnaashari, Motamedi, Asnaashari, & Azari-Marhabi, 2019).…”
Section: Discussionunclassified
“…Métodos alternativos como substâncias fitoterápicas com atividade antimicrobiana têm sido alvo de estudos também, em função do seu potencial para prevenção de doenças bucais, especialmente os que se relacionam ao biofilme oral (Jafari et al, 2015;Madeira et al, 2016;Sookto et al, 2013;Oliveira et al, 2014).…”
Section: Discussionunclassified
“…Evidence shows that Zataria multi ora (Shirazi thyme) has suitable antimicrobial and antifungal properties for irrigation of root canals in endodontic treatment in vitro, compared with chemical irrigating solutions [38,39]. Also, Zataria multi ora essential oil is effective for disinfection of acrylic plates and orthodontic elastics in vitro [40,41]. Favorable antifungal activity of T. vulgaris essential oil, compared with CHX, has also been reported for disinfection of removable orthodontic appliances in vitro [42].…”
Section: Introductionmentioning
confidence: 99%